Kinetics and Thermodynamics Studies of Glycyrrhizic Acid Adsorption Using S-8 Macroporous Resin - He, Xiujuan; Dan, Jianming; Hong, Chenglin (Asian Journal of Chemistry, 2013)
Simple method for adsorption of glycyrrhizic acid tri-ammonium salt from aqueous solution by the macroporous resin was presented in this work. Static adsorption studies were used for comparing the adsorption capacities of the nine resins, S-8, H1020, NKA, X-5, D4006, D101, AB-8, NKA-II and NKA-9, respectively. The results showed that S-8 resin had the best adsorption capacity. The maximum adsorption capacity of resin S-8 for glycyrrhizic acid tri-ammonium salt was found to be 75.06 mg/g at 303 K. Exploring the static adsorption isotherms, kinetics and thermodynamics on macroporous adsorption resin S-8 from glycyrrhizic acid tri-ammonium salt aqueous solutions. The adsorption isotherm data could be well described by the Langmuir and from which the adsorption capacity was obtained. The adsorption kinetics well fitted using a pseudo second-order kinetic model. Thermodynamic parameters (i.e., change in the free energy (DG), the enthalpy (DH) and the entropy (DS)) were evaluated and indicate that the adsorption of glycyrrhizic acid triammonium salt onto the S-8 resin was a spontaneous reaction and endothermic process.